Pelaksanaan Restitusi Dalam Putusan Mahkamah Syar’iyah Lhokseumawe Terhadap Perkara Pemerkosaan Anak (Studi Penelitian Di Mahkamah Syar’iyah Lhokseumawe) - Yanti, Asri Vivi; Muhammad Hatta; Hamdani (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2023)
Rape is sexual intercourse with the genitals or anus of another person as a victim with the perpetrator's penis or other objects used by the perpetrator or against the vagina or genitals of the victim with the mouth of the perpetrator or between the mouth of the victim and the perpetrator's penis, by force or coercion or threats against the victim. Victims are parties who are harmed and suffer as a result of someone's actions and therefore protection for victims of sexual crimes or rape is absolutely necessary to be given because of violations of their rights. Therefore, the right of restitution for victims must be carried out in accordance with the mandate of qanun Jinayat Number 6 of 2014 article 51 which regulates the granting of restitution. This study aims to analyze how the implementation of the fulfillment of the right of restitution for child victims of rape crimes in decision Number. 05/JN/2019/MS. LSM at the Lhokseumawe Syar'iyah Court and what are the obstacles in implementing the fulfillment of the right of restitution for child victims of rape crimes in decision Number. 05/JN?2019/MS.LSM at the Lhokseumawe Syar'iyah Court and how are efforts to overcome obstacles in fulfilling the right of restitution for child victims the crime of rape in decision Number. 05/JN/2019/MS.LSM at the Lhokseumawe Syar'iyah Court. This research is a qualitative research using an empirical juridical approach through the decision of the Aceh Syar'iyah Court Number 05/JN/2019/MS.LSM. Whereas the fulfillment of the right of restitution which is the right of the victim was not paid by the defendant to the victim's family, this was due to the existence of a legal void rule in Qanun Jinayat Number 6 of 2014 which did not have a forced rule in granting restitution if it was not paid by the defendant, so the prosecutor could not confiscate the victim's assets as a substitute for restitution. The results of this study indicate that there has never been a fulfillment of restitution to victims carried out by the defendant in cases of sexual harassment or finger rape due to the weakness of the rules contained in qanun jinayat which do not have coercive rules in granting restitution. It is recommended that the revision of the Qanun jinayat law Number 6 of 2014 must be implemented immediately, seeing the number of cases of criminal acts of rape against children which are increasing, while Aceh, in particular which enforces the qanun jinayat as a rule in its territory, has very many voids in the rule of law, one of which is not having efforts coercion or compensation in granting restitution to victims, taking into account Supreme Court Regulation Number 1 of 2022 judges are given the authority to adjudicate requests for restitution in the fairest way possible.